Nuclear disarmament verification via resonant phenomena - Jake J. Hecla; Areg Danagoulian (Nature Communications, 2018)
Authenticating a nuclear warhead without revealing its design is a challenge. Here the authors discuss a nuclear disarmament verification method based on neutron resonance analysis which is sensitive to the isotopic composition of the materials used in warheads.